Genetic insight into dissecting the immunophenotypes and inflammatory profiles in the pathogenesis of Sjogren syndrome - Jingyi Xu; Shucheng Si; Yijun Han; Lin Zeng; Jinxia Zhao (Journal of Translational Medicine)
Abstract Background Sjogren syndrome (SS) is a chronic systemic autoimmune disease and its pathogenesis often involves the participation of numerous immune cells and inflammatory factors. Despite increased researches and studies recently focusing on this area, it remains to be fully elucidated. We decide to incorporate genetic insight into investigation of the causal link between various immune cells, inflammatory factors and pathogenesis of Sjogren syndrome (SS). Methods Our study leveraged the genetic variants of multi-omics statistics extracted from genome-wide association study (GWAS), the University of Bristol and the FinnGen study. We performed a bidirectional Mendelian randomization and mediation study based on randomly allocated instrumental variables to infer causality, followed by external validation with UK Biobank data and Bayesian colocalization. Results We demonstrated that an elevated level of CD27 on IgD + CD24 + B cell, a subset of B cells expressing both IgD and CD24, was associated with a higher risk of SS (OR = 1.119, 95% CI: 1.061–1.179, P < 0.001), while CD3 on CD45RA + CD4 + Treg was a protective factor (OR = 0.917, 95%CI: 0.877–0.959, P < 0.001). Results of meta-analysis and colocalization further supported the significant results identified in the primary analysis. A total of 4 inflammatory cytokines and 7 circulating proteins exhibited potential causal relationships with SS despite no significant result achieved after FDR correction. Finally, results of mediation analysis indicated that CD40L receptor levels had significant mediating effects (β = 0.0314, 95% CI: 0.0004–0.0624, P = 0.0471) at a mediation proportion of 28% (95% CI: 0.364%-55.6%) in causal relationship between CD27 on IgD + CD24 + B cell and SS. Conclusions By providing a novel genetic insight into unveiling the roles of autoimmunity and inflammation in Sjogren syndrome, our findings may potentially lead to identifying new clinical biomarkers for disease monitoring and therapeutic targets that offer more effective alternatives for treating this condition. Therefore, our study may provide valuable evidence for future clinical intervention and targeted immunotherapy.